Evaluation of full S1 gene sequencing of classical and variant infectious bronchitis viruses extracted from allantoic fluid and FTA cards. Issue 4 (4th July 2018) - Manswr, Basim; Ball, Christopher; Forrester, Anne; Chantrey, Julian; Ganapathy, Kannan
ABSTRACT: Sequence variability in the S1 gene determines the genotype of infectious bronchitis virus (IBV) strains. A single RT-PCR assay was developed to amplify and sequence the full S1 gene for six classical and variant IBVs (M41, D274, 793B, IS/885/00, IS/1494/06 and Q1) enriched in allantoic fluid (AF) or the same AF inoculated onto Flinders Technology Association (FTA) cards. Representative strains from each genotype were grown in specific-pathogen-free eggs and RNA was extracted from AF. Full S1 gene amplification was achieved using primer A and primer 22.51. Products were sequenced using primers A, 1050+, 1380+ and SX3+ to obtain short sequences covering the full gene. Following serial dilutions of AF, detection limits of the partial assay were higher than those of the full S1 gene. Partial S1 sequences exhibited higher-than-average nucleotide similarity percentages (79%; 352 bp) compared to full S1 sequences (77%; 1756 bp), suggesting that full S1 analysis allows greater strain differentiation. For IBV detection from AF-inoculated FTA cards, four serotypes were incubated for up to 21 days at three temperatures, 4°C, room temperature (approximately 24°C) and 40°C. RNA was extracted and tested with partial and full S1 protocols. Through partial sequencing, all IBVs were successfully detected at all sampling points and storage temperatures. In contrast, using full S1 sequencing it was not possible to amplify the gene beyond 14 days or when stored at 40°C. Data presented show that for full S1 sequencing, a substantial amount of RNA is needed. Field samples collected onto FTA cards are unlikely to yield such quantity or quality. Abbreviations: AF: allantoic fluid; CD50: ciliostatic dose 50; FTA: Flinders Technology Association; IB: infectious bronchitis; IBV: infectious bronchitis virus